Integrin alpha L: structure, cellular functions, and emerging role in human diseases - Wang, Xianglin; Yang, Guoya; Chen, Yanpei; Zhu, Fang; Lian, Fuming; Shen, Wenzhi; Luo, Dehong (Frontiers in Immunology, 2026)
As an integral component of Lymphocyte Function-associated Antigen 1 (LFA-1), Integrin α L is crucial for the processes of leukocyte adhesion and migration. It engages in specific interactions with Inter-Cellular Adhesion Molecules (ICAMs), thereby playing a significant role in intercellular adhesion, signal transduction, immune response regulation, inflammatory pathways, and the intricate formation of the tumor microenvironment. While preliminary studies have begun to elucidate the phenotypic diversity and bioinformatic characteristics of Integrin α L across various diseases, there remains a paucity of comprehensive reviews addressing the functional roles and underlying mechanisms of Integrin α L in different pathological contexts. This review aims to delineate the fundamental structure and function of Integrin α L, while also summarizing the relationship between its expression patterns and functional attributes with respect to the invasive potential, metastatic capabilities, immune evasion strategies, and clinical outcomes of tumor cells and patients across a spectrum of tumor types. Furthermore, we highlight the significant involvement of Integrin α L in non-tumor-related diseases, including atherosclerosis, systemic sclerosis, depression, and rheumatoid arthritis. Additionally, we assess the potential of Integrin α L as a molecular biomarker for the diagnosis of specific diseases and tumors, which may pave the way for novel therapeutic targets in the treatment of associated conditions and malignancies.